Juigchen in den adel der menschelijke natuur. Het verhevene in de Nederlanden (1770-1830) - Christophe, Madelein (Academia Press, 2021)
A storm at sea, hanging cliffs, volcano eruptions at night, threatening thunderclouds over a desolate mountain landscape: all these phenomena incite both fear and pleasure, astonishment and fascination. We call them sublime, after the feeling of the sublime. In the eighteenth century the sublime became the exciting alternative to the beautiful. The concept has ancient roots, but branches out into French, British, German, and Dutch cultures. Stemming originally from rhetoric, in the course of the eighteenth century it became an aesthetic, philosophical and literary concept. In this study the history of the sublime is told for the first time in Dutch. This book focuses on Dutch contributions on the sublime, in the light of the international history of the concept of the sublime. From the earliest translations to the original ideas of Johannes Kinker and Willem Bilderdijk: the Dutch sublime reflects both the entwinement with the European Enlightenment and the specific nature of Dutch culture in the long eighteenth century.